Effect Of Polymer Molecular Weight On The Luminescence Properties Of Nanocomposite Zinc Oxide/Polyethylene Glycol - M. Abdullah (Dept. of Chemical Engineering, Diponegoro University, 2003)
Luminescence Properties Of Nanocomposite (Zinc Oxide/Polyethylene Glycol: Lithium ions) have been synthesized using different molecular weight of polymer. Changing the molecular weight produced no effect of the crystallinity of ZnO nanoparticles if similar molarity of ethylene glycol unit were used. However, the use of high molecular weight of polymers tended to reduce the size of nanoparticles, which implied to the enhancement in the luminescence spectra due to increasing in the particle number concentration. TEM picture of sample prepared using PEG of molecular weight 0f 500,000 exhibitef a particle size of 5 nm, which was close to the value predicted y Waaent-Schere formula or size dependent band gap.Keywords : nanocomposite, luminescent polymer electrolytes, zinc oxide, polyethylene glycol